2020
DOI: 10.3390/ijerph17072512
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Diagnosis of Flexibility Preparation of Male Sport Climbers

Abstract: The objective of the study was to verify the relationships between sport skill levels and to identify the tests that accurately diagnose flexibility of sport climbers. This study examined 60 competitive advanced–higher elite male 7b–9a redpoint (RP) climbers. The athletes performed commonly used flexibility tests (stand-and-reach, straddle sit, straddle stand) and climbing-specific flexibility tests. Significant correlations were found between sport skill levels for the straddle stand test (r = −0.48) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The OpenPose model was chosen for its satisfactory performance and ease of implementation in the Matlab environment [23] [24]. Access to such information provides the possibility of obtaining additional parameters useful for analyzing the climber's movement [25] in the biomechanical aspect or achieving joint mobility [26].…”
Section: Video Recording and Parameters Obtained From Computer Video ...mentioning
confidence: 99%
“…The OpenPose model was chosen for its satisfactory performance and ease of implementation in the Matlab environment [23] [24]. Access to such information provides the possibility of obtaining additional parameters useful for analyzing the climber's movement [25] in the biomechanical aspect or achieving joint mobility [26].…”
Section: Video Recording and Parameters Obtained From Computer Video ...mentioning
confidence: 99%
“…As this difference was not found for resting masticatory muscle activation, the authors hypothesized that teeth clenching might be conducted regularly during climbing. Draga et al [ 13 ] aimed to investigate the relationship between climbing performance and several flexibility tests in climbers of advanced to higher elite level. The authors reported moderate-to-large correlation coefficients between climbing performance and hip flexibility [ 13 ].…”
Section: Mountaineering and Climbingmentioning
confidence: 99%
“…Draga et al [ 13 ] aimed to investigate the relationship between climbing performance and several flexibility tests in climbers of advanced to higher elite level. The authors reported moderate-to-large correlation coefficients between climbing performance and hip flexibility [ 13 ]. Higher climbing performance was associated with larger hip abduction flexibility assessed by standard, non-climbing specific flexibility tests.…”
Section: Mountaineering and Climbingmentioning
confidence: 99%
“…However, one study showed that athletes performed commonly used flexibility tests (stand-and-reach, straddle stand) and climbing-specific flexibility tests. Significant correlations were found between sport skill levels for the straddle stand test (r = −0.48), and the straddle sit test (r = −0.41) [19].…”
Section: Introductionmentioning
confidence: 98%